Disrupting HBV Persistence: Genetic Engineering Approach to Break the Oncogenic HBx Gene - Saleha Resham; Haiqa Khan; Fazal Adnan; Sobia Manzoor (NUST Journal of Engineering Sciences)
Chronic Hepatitis B virus (HBV) infection can cause liver cirrhosis or cancer , making it a persistent worldwide health concern. Nucleoside analogs used in current antiviral treatments can prevent HBV from replicating, but they do not break the covalently closed circular DNA that HBV currently possesses.